Pendampingan Pembuatan Media Pembelajaran Bagi Mahasiswa Paud STAI Darussalam Lampung - Oktavianti, Sinta; Oktaviana, Anita (Yayasan Daarul Huda Kruengmane, 2025)
Learning media is a tool for delivering messages from the teacher as the giver of the message to the learner as the receiver. Learning media is very helpful for the learning success of children in school so that children can grasp the material well. As for this accompanying activity aims to give insight to students of kindergarten STAI Darussalam Lampung in making the right learning media while teaching. This method of serving the community using Service Learning, is implemented through multiple steps namely planning, implementation and evaluation. As for the results obtained that is students are able to create learning media in accordance with the learning theme. Through the creation of this learning medium, students can stimulate their imagination, creativity and cognitive powers. With this companionship, students (prospective teachers) of early childhood education can finally deliver teaching materials that are interesting, meaningful and of course fun for their learners.